Genotoxicity and antimicrobial activity of Myrtus communis L., Ziziphus spina-christi (L.) Willd and Cassia angustifolia Vahl extracts (Bangladesh Journal of Botany, 2020)
Genotoxicity and antimicrobial activity of the leaf extract of Myrtus communis, Ziziphus spina-christi and Cassia angustifolia plants were evaluated. The prophage induction assay was used to test the genotoxicity. The results showed that, no fold increase in Pfu/ml over the spontaneous release for F116 and R3 phages, so these results indicated that Myrtus communis, Ziziphus spina-christi and Cassia angustifolia leaves extract did not have genotoxic effect, so they can be used as antimutagen. On the other hand, Myrtus communis and Ziziphus spina-christi showed strong antimicrobial activity against all tested microbes. The antimicrobial effect increased by the increase of the concentration. While Cassia angustifolia leaves extract showed moderate antimicrobial activity against some strains. The results of antimicrobial activity suggest that these plant extracts have cytotoxic effect.